Implementasi program bina pribadi Islam (BPI) dalam menanamkan pendidikan karakter religius siswa di SMK Islam Inayah Kecamatan Ujung Batu Kabupaten Rokan Hulu - Aswanda, Jais; Dewi, Eva; Murniati , Andi (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2024)
This study aims to describe the implementation of the Islamic Personal Development Program (BPI) in instilling religious character education for students at SMK Islam Inayah Ujungbatu. The approach used is qualitative descriptive with interview, observation, and documentation data collection techniques. Primary data was obtained from respondents, while secondary data was obtained through school libraries and archives. The results of the study show that: 1) The BPI program is a flagship program at SMK Islam Inayah, requiring careful planning, implementation, and evaluation, 2) The BPI program is implemented in two patterns: intracurricular (Islamic Study Club, zikir al-matsurat) and extracurricular (iftor jama'i, MABIT, Rihlah, BPI Fit Camp, humanitarian care action), 3) The strengthening of students' religious character is seen in daily life, including the character of faith and piety,  honesty, responsibility, help, keeping promises, caring for the environment, and caring for society.